Strategi Transformasi Bisnis Berkelanjutan Melalui Adopsi Teknologi Digital Dan Green Innovation Pada Perusahaan Di Indonesia - Khairunnisa (CV. SINAR HOWUHOWU, 2025)
Sustainable business transformation has become a crucial strategy for companies to address the challenges of globalization, climate change, and the Fourth Industrial Revolution. This study aims to analyze sustainable business transformation strategies through the adoption of digital technology and green innovation among companies in Indonesia. A descriptive qualitative approach was applied, utilizing in-depth interviews, observation, and document analysis in several firms that have implemented digitalization and environmental innovation. The findings reveal that the adoption of digital technologies significantly enhances energy efficiency, operational transparency, and the effectiveness of green supply chains. Meanwhile, green innovation contributes to competitiveness by improving resource efficiency and corporate reputation. The integration of both strategies creates synergy that fosters simultaneous economic, social, and environmental value creation. However, this study also identifies challenges such as limited human resource capacity, insufficient digital infrastructure, and inadequate governmental policy support for green innovation. Therefore, the findings reinforce the argument that combining digitalization and green innovation forms a foundational strategy for sustainable business in the future.